1988
DOI: 10.1039/ap9882500381
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in atomic and molecular spectroscopy

Abstract: The following are summaries of three of the papers presented a t a Joint Meeting of the North East Region and Atomic Spectroscopy and Molecular Spectroscopy Groups held on March 29th-30th, 1988, in the University of Hull.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The principles and application of partial least squares (PLS) regression and principal component regression in spectrometry have been discussed by several researchers . Recently, the combination of derivative techniques with multivariate calibration methods has been proposed, and the convenience of such an approach has been evaluated by several workers with contradictory results . In this work, a spectrophotometric method has been developed for simultaneous analysis of binary mixtures of dyes (BG and MG) in synthetic samples and some wastewater samples with applying PLS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The principles and application of partial least squares (PLS) regression and principal component regression in spectrometry have been discussed by several researchers . Recently, the combination of derivative techniques with multivariate calibration methods has been proposed, and the convenience of such an approach has been evaluated by several workers with contradictory results . In this work, a spectrophotometric method has been developed for simultaneous analysis of binary mixtures of dyes (BG and MG) in synthetic samples and some wastewater samples with applying PLS.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Recently, the combination of derivative techniques with multivariate calibration methods has been proposed, and the convenience of such an approach has been evaluated by several workers with contradictory results. [19][20][21] In this work, a spectrophotometric method has been developed for simultaneous analysis of binary mixtures of dyes (BG and MG) in synthetic samples and some wastewater samples with applying PLS. In addition, the original and first derivative absorption spectra of the binary mixtures were used to perform the optimization of the calibration matrices by the PLS method.…”
mentioning
confidence: 99%
“…Martens and co-workers [10][11][12] quantified three botanical components, pericarp, aleurone and endosperm, by using several emission scans, recorded at different excitation wavelengths, characteristic of each of the mixture components. Jones et al 13 reported the use of excitation, emission and synchronous spectra for the determination of acyclovir and guanine.…”
mentioning
confidence: 99%
“…However, their convenience is contradictory. [15][16][17] In this work, the resolution of the ternary mixtures of carbofuran, carbaryl and fenamiphos by extraction-UV spectrophotometry was carried out, using the chemometric methods second-derivative ratio spectra, CLS, PCR, and PLS (types 1 and 2). A comparison of the results obtained in the analysis of synthetic samples by the different methods applied was made by using analysis of variance (ANOVA).The data used were the absorption spectra and their transformations (logarithm or derivative) and these data were preprocessed in different ways (mean centring or variance scaling).…”
mentioning
confidence: 99%